2021
DOI: 10.1007/s00402-020-03747-2
|View full text |Cite
|
Sign up to set email alerts
|

No implant, no solution, lost cases to surgery: orthopedic trauma triage for surgery in an NGO hospital in Sierra Leone

Abstract: Introduction In low-income countries (LIC), international surgeons face the fact that there are patients they cannot treat. The goal of this study was to identify and analyze patients lost to treatment. Material and methods We analyzed retrospectively the data of 282 trauma victims from a non-governmental organizational (NGO) hospital in Sierra Leone, Africa. During a 3-month period (10.10.2015–08.01.2016), these patients had 367 injuries and underwent 263… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Kilonzo et al reported that 92.3% of unstable ankle fractures managed conservatively resulted in complications compared with 37.5% of operatively managed unstable fractures. Four papers did not define the presence or absence of complications other than infection at follow-up [19,20,22,28].…”
Section: Closed Fracturesmentioning
confidence: 99%
“…Kilonzo et al reported that 92.3% of unstable ankle fractures managed conservatively resulted in complications compared with 37.5% of operatively managed unstable fractures. Four papers did not define the presence or absence of complications other than infection at follow-up [19,20,22,28].…”
Section: Closed Fracturesmentioning
confidence: 99%
“…Our results are consistent with previous studies that found that hospitals in these countries still face widespread deficiencies in trauma capacity, 39 and limited implant availability may be a key contributor. 40 However, these differences in preferred treatment could be because of lack of access to equipment and/or inadequate dissemination of knowledge, as intramedullary nailing has become an increasingly available method of fracture fixation in lowresource settings 41 and has been shown to be cost-effective 42,43 with improved early functional recovery and lower risk of malunion in LMICs. 44 Respondents reported not having sufficient experience with the procedures, not having the necessary equipment, or a combination of both, but our survey was not designed to detect whether one reason was more predominant than the other.…”
Section: Discussionmentioning
confidence: 99%
“…This study was developed is an NGO hospital located in Goderich, Freetown, Sierra Leone, active since 2001 where all the patients are treated free of charge, the hospital is equipped with 85 beds, divided in an intensive care unit with eight beds, an operating theatre with three operating rooms, six wards, an outpatient department, a dressing room, an X-ray room, a physiotherapy room, and a casting room [ 8 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…In many LMIC, hospital resources are sometimes dependent on non-governmental and humanitarian organizations (NGO) and the most commonly used or available osteosynthesis materials in low-resourced settings include external fixators, conventional non-locking plates and intramedullary nails [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%